Studi Literatur Efektivitas Simplisia Daun Seledri (Apium graveolens L) terhadap Penurunan Tekanan Darah pada Penderita Hipertensi - Aulia Ulhanifah Andiani; Cindy Syahira Ananta; Hutry Inayah Marzuki; Khairifaldi Praditya; Kiki Sundari; Shafira Nursyamsiah Khamila; Dwintha Lestari (TRILOGI: Jurnal Ilmu Teknologi, Kesehatan, dan Humaniora, 2025)
Blood pressure control can be achieved through both pharmacological and non-pharmacological therapies, one of which involves the use of celery leaves (Apium graveolens L.). This study aims to review the effectiveness of dried celery leaf simplicia in reducing blood pressure and its potential as a basis for transdermal patch formulation. A qualitative literature review was conducted using inclusion criteria comprising original research and review articles discussing celery leaves as antihypertensive agents, published within the last ten years, available in full text, and relevant to the research topic. Irrelevant articles, duplicates, and studies lacking outcome data were excluded from the analysis. The review results indicate that celery leaves contain major groups of bioactive compounds, including flavonoids, alkaloids, saponins, and phenolic compounds, which exhibit diuretic, vasodilatory, and antioxidant activities. Based on several experimental and clinical studies analyzed, administration of celery leaf decoction was reported to reduce systolic blood pressure by approximately 24–30 mmHg and diastolic blood pressure by 7–10 mmHg, with variations observed among studies. The antihypertensive mechanisms involve increased nitric oxide (NO) production, inhibition of the angiotensin-converting enzyme (ACE), and diuretic effects. In addition, the physicochemical characteristics of celery leaf bioactive compounds indicate their potential for formulation into transdermal patch systems intended for patients with mild to moderate hypertension, defined by blood pressure levels ≥140/90 mmHg and <180/110 mmHg. The limitations of this review include variations in dosage, extraction methods, and study designs across the analyzed literature. In conclusion, celery leaf simplicia demonstrates potential antihypertensive effects with minimal side effects, and the development of transdermal patches represents an innovative approach that requires further validation through clinical trials.